TITHING IN UGARIT AND THE PENTATEUCH – POSSIBLE IMPLICATIONS FOR AFRICA - Ajah, Miracle (Scriptura, 2006)
The thesis of this paper is stating that a rigorous study and theological interpretations of the different examples of tithing in Ugarit and the Pentateuch can motivate a more reflected theological-ethical understanding and the practice of tithing amongst believing communities in Africa. The tithe demanded that the people serve their God at a significant cost to themselves. An appeal is made to the Church in Africa to consider how to mobilize support for her projects through the application of their theological-ethical understanding of tithing.